2019
DOI: 10.1111/1348-0421.12748
|View full text |Cite
|
Sign up to set email alerts
|

Change in membrane potential induced by streptolysin O, a pore‐forming toxin: flow cytometric analysis using a voltage‐sensitive fluorescent probe and rat thymic lymphocytes

Abstract: Streptolysin O (SLO) is a bacterial pore‐forming toxin that is employed to permeabilize cell membranes in some biological experiments. SLO forms various types of pores with different shapes, increasing membrane ion permeability and subsequently inducing changes in membrane potential. To characterize the pores formed by SLO, the changes in membrane potential induced by SLO in rat lymphocytes were considered using flow cytometry with a voltage‐sensitive fluorescent probe, bis‐(1,3‐dibutylbarbituric acid)trimethi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Following a rather timeconsuming permeabilization process of 6 h, mean pDNA transfection efficiencies of 15% could be achieved in PBMCs (Nateri et al, 2005). Permeabilization of the T cell membrane can also be obtained by bacterial pore-forming toxins, such as Streptolysin-O (SLO) (Alexander et al, 1989;Kobayashi et al, 2020) or Lysenin (Shrestha et al, 2020), although the applicability of these toxins for T cell engineering remains largely unexplored. This is not surprising, knowing that the generated pore sizes are limited to delivery of macromolecules <150 kDa (Walev et al, 2001), which makes it incompatible with most of the effector molecule types for T cell engineering (Stewart et al, 2018).…”
Section: Soluporationmentioning
confidence: 99%
“…Following a rather timeconsuming permeabilization process of 6 h, mean pDNA transfection efficiencies of 15% could be achieved in PBMCs (Nateri et al, 2005). Permeabilization of the T cell membrane can also be obtained by bacterial pore-forming toxins, such as Streptolysin-O (SLO) (Alexander et al, 1989;Kobayashi et al, 2020) or Lysenin (Shrestha et al, 2020), although the applicability of these toxins for T cell engineering remains largely unexplored. This is not surprising, knowing that the generated pore sizes are limited to delivery of macromolecules <150 kDa (Walev et al, 2001), which makes it incompatible with most of the effector molecule types for T cell engineering (Stewart et al, 2018).…”
Section: Soluporationmentioning
confidence: 99%
“…Many investigations on host cellular response to major streptococcal and nonstreptococcal CDCs such as PLY produced by S. pneumoniae , 83 LLO produced by Listeria monocytogenes , 84 and PFO produced by C. perfringens 85 have been conducted and reported as review articles. Concerning the SLO produced by S. pyogenes , the induction of change in membrane potential of rat thymic lymphocytes 86 and the induction of long‐lasting intracellular Ca 2+ oscillation via IP 3 ‐mediated depletion of intracellular store 87 were reported. It was also reported that PLY upregulates the expression of P 2 X 7 receptor and induces the cytotoxicity 88 .…”
Section: Cholesterol‐dependent Cytolysinsmentioning
confidence: 99%